IMPLEMENTASI PUBLIC RELATION DALAM CYBERCOMMUNITY - Halim Setiawan (Syi’ar: Jurnal Ilmu Komunikasi, Penyuluhan dan Bimbingan Masyarakat Islam, 2019)
Society is not only a permanent social structure, but a very complex social process. This means that the community within itself will continue to experience changes. Changes in social life occur due to the global impact of the modernization process and the new challenges faced by society. Cybercommunity or virtual society is a revolution against a real change in society. The development of information technology is not only able to create a global community, but materially it is able to develop a new life space for the community, so that without realizing it, the human community has lived in two worlds of life, namely the life of the real community and the life of the virtual community (cybercommunity). Communication relations between communities can be created by institutions with the help of public relations which play a role in establishing good communication between the institution and the community.